The potential of crop residues, particularly wheat straw, as livestock feed in Ethiopia - Gebrehiwot, L.; Mohammed, J. (International Livestock Centre for Africa, 1989)
Reviews the extent and use of crop residues as livestock feeds in Ethiopia with special emphasis to wheat with respect to varietal difference and agronomic practices to enhance the utilisation of the straw. Lists area and yield of major crops in Ethiopia. Presents data on yield & chemical composition of various crop residues, weight gains of steers fed crop residue, and effect of N fertilization on grain yield and quality & quantity of wheat straw. Also summarises results of an undersowing trials of forage crops to wheat.